The Effect of Training on Employee Performance Improvement: Case Study of Matahari Bangkalan Plaza Store - Ismi Millah Tibyana; Yunita Agustini; Nurul Nabila; Iriani Ismail (International Journal of Economics and Management Research, 2025)
Employee training is a crucial element in enhancing individual and organizational performance. This study aims to analyze the impact of training on employee performance at Store Matahari Bangkalan Plaza. Using a qualitative approach, data was collected through in-depth interviews with 10 employees who participated in training programs. The findings indicate that training positively contributes to improving work skills, motivation, productivity, and adaptability to workplace changes. Additionally, training enhances the quality of customer service. Therefore, companies should develop more systematic and continuous training programs to ensure optimal employee performance.